Experimental study of wire electrical discharge machining of AISI D5 tool steel - Hasçalyk, A; Çaydas, U (Elsevier Science Sa, 2004)
This paper presents an experimental investigation of the machining characteristics of AISI D5 tool steel in wire electrical discharge machining process. During experiments, parameters such as open circuit voltage, pulse duration, wire speed and dielectric fluid pressure were changed to explore their effect on the surface roughness and metallurgical structure. Optical and scanning electron microscopy, surface roughness and microhardness tests were used to study the characteristics of the machined specimens. Taking into consideration the experimental results, it is found that the intensity of the process energy does affect the amount of recast and surface roughness as well as microcracking, the wire speed and dielectric fluid pressure not seeming to have much of an influence. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: WEDM process; surface integrity; AISI d5 tool steel